The identification of technology regimes in banking: Implications for the market power-fragility nexus - Koetter, Michael; Poghosyan, Tigran (Journal of Banking & Finance, 2009)
Neglecting the existence of different technologies in banking can contaminate efficiency, market power, and other performance measures. By simultaneously estimating (i) technology regimes conditional on exogenous factors, (ii) efficiency conditional on risk management, and (iii) Lerner indices of German banks, we identify three distinct technology regimes: Public & Retail, Small & Specialized, and Universal & Relationship. System estimation at the regional level reveals that greater bank market power increases bank profitability but also fosters corporate defaults. Corporate defaults, in turn, lead to higher probabilities of bank distress, which supports the market power-fragility hypothesis.